Effect of single and repeated waterlogging events on tropical forage grasses for cut and carry systems - Rowan W. Smith; Thi Mui Nguyen; Nguyen Xuan Ba; Nguyen Huu Van; Jeff P. Corfield; David Parsons (Tropical Grasslands-Forrajes Tropicales)
The introduction of improved forage cultivars has enhanced nutrition and performance of beef cattle in stall feeding cut and carry systems in Vietnam and other Southeast Asian countries. However, the persistence of these forages can be reduced by flooding and waterlogging conditions in low-lying land during the monsoon season. This pot study was established with 5 waterlogging treatments (control, 10-day single, 10-day cycle, 20-day single, and continuous waterlogging) for an 84-day period following establishment to evaluate the waterlogging tolerance of 7 improved grass cultivars. Urochloa humidicola (Rendle) Morrone & Zuloaga, Paspalum atratum Swallen. and Digitaria eriantha Streud. were most tolerant of waterlogging. Tiller number and dry matter production were negatively affected by cycling and continuous waterlogging in less tolerant species Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs, Urochloa hybrid ‘Mulato II’ and Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins. This information will assist in providing recommendations for smallholder farmers about which species to grow under repeated or continuous waterlogging.